The nineteenth-century politics of autoethnography and nationalism in the novels of Morier and Morgan - Öz, Özge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2020., 2020)
This study explores the representations of nationhood and national identity in the context of British and Ottoman Empires in two nineteenth century English novels, the English writer James Justinian Morier’s Ayesha, the Maid of Kars (1834) and the Anglo-Irish writer Lady Morgan’s Woman, or Ida of Athens (1809). Drawing from the theories of nationalism, colonialism, and orientalism as well as the literary theory of Frederic Jameson, this thesis aims to examine the political unconscious of these two novels emerging from their comparative attitude towards the nationhood of the British and Ottoman Empires. Being respectively related to the genres of travel writing and national tale, Morier and Morgan’s novels are identified as examples of nineteenth-century British autoethnographic literature. Accordingly, the representing of a colonized and Orientalized Other emerges as a vital means for arriving at an English autoethnography in both novels. Differentiating between their depictions of civic and ethnic nationalism in British and Ottoman contexts, I argue that the novels’ assignation of civic nationhood to the British Empire and ethnic nationhood to the Ottoman Empire bespeak their orientalist and colonialist political unconscious. Ultimately, I also find that the close study of nationality in both novels force the concept of national identity to emerge as a social construct as in the understanding of modernist nationalism, dependent on appropriation and performativity.